Cross-cultural Adaptation and Validation of Patient Safety Culture Assessment Tool for Clinical Staff in Kazakhstan - Kyrykbayeva, Saltanat; Semenova, Yuliya; Goremykina, Maiya; Moldagaliyev, Timur; Kauysheva, Almagul; Azizov, Sharafaddin; Trinchero, Elisabetta (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Modern healthcare systems lack empirical models and appropriate tools to evaluate the safety culture, which encourages the need for their development. The national healthcare system of Kazakhstan has no empirically tested robust tools to evaluate the safety culture. AIM: The present paper aims at performing translation, cross-cultural adaptation, and validation of the “Patient safety culture” tool (from here – the tool) as a means for evaluating safety culture in healthcare establishments of the Republic of Kazakhstan. METHODS: The study design was cross-sectional. The original “Patient safety culture” tool is an integrated evaluation framework consisting of 7 scales and 62 items (6 general questions and 56 targeted questions) and reflecting different aspects of risk-related components of safety culture. The Cronbach’s alpha coefficient ranging from 0.0 to 1.0 was used to measure the internal consistency of the tool. To evaluate the tool’s reproducibility, we performed a test-retest assessment after 15 days and evaluated it using Pearson’s correlation coefficient. RESULTS: The overall Cronbach’s alpha for different scales ranged from 0.27 to 0.75. Subscales “Safety procedures” and “Safety Training” had the lowest coefficients. At test-retest, the Pearson’s correlation coefficient ranged from 0.934 to 0.969 among the scales. CONCLUSION: The study is dedicated to cross-cultural adaptation and validation of the “Patient safety culture” tool and describes the development of a translation protocol with subsequent cognitive debriefing and field testing. The field testing helped to confirm good validity, reliability, and reproducibility. The tool might undergo additional modification after further testing.